Changing lesion demographics of the adult with congenital heart disease: an emerging population with complex needs. (March 2012) - Stuart, Alan Graham
The demography of congenital heart disease is changing. Largely as a consequence of successful cardiac surgery in childhood, there are an increasing number of adults with congenital heart disease with a prevalence of more than four per 100 adults. The type of disease in adults is also changing with an increasing number of survivors with complex disease. These patients have a significantly increased healthcare requirement in comparison to healthy adults and this includes noncardiac, multisystem morbidity. The adult congenital heart disease population are now developing problems associated with aging and there is a new population of geriatrics with congenital heart disease. As survival continues to improve, increased healthcare resources need to be directed towards the management of the adult with congenital heart disease.